Atención al cliente en el Comercial Fashggion Center en la Parroquia San Juan del 2022. - Vinces Terranova, Estefany Daniela (2023)
This case study deals with customer service in the Fashion Center commercial in the San Juan parish, it was carried out in order to know and identify if the service used by the company was adequate and to know the level of consumer satisfaction. The existing problems were described based on the quality of the products and the service that was offered to them and as an objective the attention process was analyzed, evaluating the sales techniques that the company used, to maintain the loyalty of its clients and how this affected For commercial sales, the method used was the user experience that allowed us to know the perspectives that consumers had of the company. The techniques and instruments that were applied to collect information were: the FODA matrix that was applied to identify the internal and external factors of the company and a survey carried out on the commercial clients to find out their needs and preferences. Obtaining results that allowed us to conclude that the attention they provided was deficient, for which effective sales strategies were proposed, which provided detailed information on what should be modified in the company, how they should improve their attention service and the quality of the products. All this will allow you to increase your sales, differentiate yourself from the competition, achieve greater recognition in the market by achieving your purpose of satisfying and retaining customers.